PERBUDAKAN DALAM PANDANGAN ISLAM HADITH AND SIRAH NABAWIYYAH: TEXTUAL AND CONTEXTUAL STUDIES - Abdul Hakim Wahid (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2015)
This paper  proves  that the law of slavery in Islam is just steps  to abolish  slavery gradually and  not to legalize it. This paper  was written  to refute  the conclusions Western orientalists, especially  Robert Morey who assume that Islam justifies slavery as embodied in the Qur’an and the Prophet’s  life history as the basis of false allegations against the Prophet and Islam